FROM "OUTSIDER WITHIN" TO "OUTSIDER WITH US" - Harrison, Faye Venetia; Goncalves Junior, Sara Wagner Pimenta (Interfaces Científicas - Educação, 2020)
Interview invitation sent to Faye Harrison, in a moment really memorable and very important to me (and my community) as transgender and latin american woman. The audience was primarily the Journal (RE-DOC - UERJ) but for the late insertion, we find another productions of researchers in education interested in race, xenophobia, indentity and interested too in gender studies and also, we try to summarize what the education is talking about, when we talk about you, how you know and felt when you had been here at UERJ. That is something interesting because you are mainly working [in] gender, identity and race. You have around mostly with "outsider within" working here, but still the impact of your work and your earlier work is still connected to your nowadays writings. And now that you are promoting your book "Decolonizing Anthropology: Moving Further toward an Anthropology for Liberation," I think people want to know your opinion about what we are doing here in terms of theory itself that can be connected to education.